Cylindrical lithium-ion battery and preparation method and application thereof
Patent Information
- Application Number
- CN202611261894.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]本发明的目的之一在于提供一种圆柱锂离子电池,能够解决圆柱锂离子电池单纯依赖高面密或高压实获得约4Ah容量所导致的高倍率极化和温升的问题
本发明提供的圆柱锂离子电池,一方面,在容量约4Ah前提下,增加正极单面活性面积,降低等效面容量和双面等效面电流密度,使得40A、50A和60A放电下的极化和温升得以降低;另一方面,负极料区长度和宽度相对正极料区外扩,使得长极片卷绕结构在端部和边缘区域保持较好的负极承接能力;同时,配合高镍层状正极、人造石墨与硅碳材料复合负极、适度N/P值和负极薄集流体,能够在不牺牲4Ah级容量情况下,有效提升恒功率放电时间和大倍率循环容量保持率,倍率极化更低,循环表现更稳定。总之,本发明通过协同设计料区长度、活性面积、等效面容量、面电流密度、负极相对长度及材料体系,达到了提升高倍率放电、恒功率输出和大倍率循环性能的技术效果。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of lithium-ion batteries, and in particular to a cylindrical lithium-ion battery, its preparation method, and its applications. Background Technology
[0002] Cylindrical lithium-ion batteries are widely used in power tools, garden tools, light power equipment, and high-power energy storage devices. For cylindrical cells with a capacity of approximately 4Ah, the market typically demands high capacity, low internal resistance, low rate-induced temperature rise, long constant power output time, and good high-rate cycle life. In traditional designs, to achieve a capacity of approximately 4Ah within a limited casing space, methods such as increasing the areal density of the positive and negative electrode coatings, increasing the compaction density, or increasing the capacity of the active material are commonly used. However, a higher areal capacity increases the diffusion distance of lithium ions along the thickness of the active material layer, which can easily lead to concentration polarization, ohmic heat, and exacerbated interfacial side reactions under high-rate discharge conditions such as 40A, 50A, and 60A. Existing technologies also reduce internal resistance and improve cycle performance by changing the positive electrode active material, negative electrode active material, or electrolyte additives. However, if the effective reaction area of the electrode is insufficient, the same discharge current is still concentrated on a small area, and the current density per unit area remains high. Especially in high charging current and high discharging current combined cycling, the lithium delithiation flux on the positive electrode side and the lithium insertion flux on the negative electrode side increase simultaneously, which can easily lead to local temperature rise, end lithium plating or cycle capacity decay.
[0003] In view of this, the present invention is hereby proposed. Summary of the Invention
[0004] One of the objectives of this invention is to provide a cylindrical lithium-ion battery that can solve the problems of high-rate polarization and temperature rise caused by the cylindrical lithium-ion battery relying solely on high surface density or high compaction to obtain a capacity of about 4Ah.
[0005] The second objective of this invention is to provide a method for preparing a cylindrical lithium-ion battery.
[0006] The third objective of this invention is to provide an application of a cylindrical lithium-ion battery.
[0007] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: In a first aspect, a cylindrical lithium-ion battery, wherein the equivalent positive electrode surface capacity Q of the cylindrical lithium-ion battery is... p 1.80mAh / cm 2 -2.25mAh / cm 2 ; The equivalent positive electrode current density J of the cylindrical lithium-ion battery during 40A discharge is... 40 18mA / cm 2 -22.04mA / cm2 The double-sided equivalent positive electrode current density J during 50A discharge. 50 22mA / cm 2 -27.55mA / cm 2 The double-sided equivalent positive electrode current density J during 60A discharge. 60 27mA / cm 2 -33.06mA / cm 2 ; The length L of the positive electrode region of the cylindrical lithium-ion battery p The width W of the positive electrode material area is 1500mm-1850mm. p The length L of the negative electrode material region is 59mm-62mm. n The length L of the positive electrode material region is greater than that of the positive electrode material region. p Width W of the negative electrode material region n The width W of the positive electrode material region is greater than that of the positive electrode material region. p ; The positive electrode active material in the positive electrode material region includes a high-nickel layered lithium transition metal oxide. The negative electrode active material in the negative electrode material region includes artificial graphite and silicon carbide materials; The equivalent negative electrode surface capacity Q of the cylindrical lithium-ion battery n With equivalent positive electrode surface capacity Q p The ratio N / P is 1.02-1.09.
[0008] Furthermore, the discharge capacity C of the cylindrical lithium-ion battery when discharged from 0.2C to 2.5V is 3800mAh-4300mAh.
[0009] Furthermore, the cylindrical lithium-ion battery has a maximum surface temperature of no more than 78°C when discharged at 60A at 25°C and 100% SOC, and a capacity retention rate of no less than 88% after 600 cycles of charging at 8A and discharging at 40A at 25°C.
[0010] Furthermore, the length L of the positive electrode material region p The width W of the positive electrode material area is 1700mm-1800mm. p It is 60mm-61mm; Preferably, the length L of the negative electrode material region n The length L of the positive electrode material region p 30mm-90mm larger; Preferably, the width W of the negative electrode material region n Width W of the positive electrode material region p Larger by 1mm-3mm.
[0011] Furthermore, the equivalent positive electrode surface capacity Q p1.86mAh / cm 2 -2.05mAh / cm 2 ; Preferably, the single-sided active area S of the positive electrode p 900cm 2 -1120cm 2 The preferred size is 1020cm. 2 -1100cm 2 ; Preferably, the single-sided active area S of the negative electrode n With the positive electrode single-sided active area S p The ratio is 1.03-1.12.
[0012] Furthermore, based on transition metal elements, the molar percentage of nickel in the high-nickel layered lithium transition metal oxide is 80%-93%.
[0013] Furthermore, the areal density of the positive electrode sheet on one side is 9.8 mg / cm³. 2 -11.3mg / cm 2 The preferred concentration is 10.2 mg / cm³. 2 -10.9mg / cm 2 ; Preferably, the compaction density of the positive electrode sheet is 3.40 g / cm³. 3 -3.60g / cm 3 The preferred value is 3.45 g / cm³. 3 -3.55g / cm 3 .
[0014] Furthermore, the mass percentage of silicon-carbon material in the negative electrode active material is 3%-10%; Preferably, the areal density of the negative electrode sheet on one side is 4.7 mg / cm³. 2 -5.8mg / cm 2 ; Preferably, the compaction density of the negative electrode sheet is 1.42 g / cm³. 3 -1.58g / cm 3 ; Preferably, the negative electrode current collector comprises copper foil; Preferably, the thickness of the negative electrode current collector is 5μm-7μm.
[0015] Furthermore, the electrolyte used in the cylindrical lithium-ion battery includes lithium salt, organic solvent, and additives. Preferably, the lithium salt comprises lithium hexafluorophosphate; Preferably, the organic solvent includes at least one of cyclic carbonates, chain carbonates, and low-viscosity cosolvents of acetates; Preferably, the additives include at least one of lithium difluorophosphate additives, fluorocarbonate film-forming additives, sulfonate lactone additives, and boron-containing lithium salt additives. Preferably, based on the total mass of the electrolyte, the electrolyte contains 0-15.0% by mass of acetate-based low-viscosity co-solvent, 2.0%-2.5% by mass of fluorocarbonate-based film-forming additives, and 0.5%-1.0% by mass of lithium difluorophosphate additives; Preferably, the separator width used in the cylindrical lithium-ion battery is greater than the width W of the negative electrode material region. n ; Preferably, the width of the diaphragm is 63.5mm-66.5mm; Preferably, the length of the separator is greater than the length L of the negative electrode material region. n ; Preferably, the length of the separator is proportional to the length L of the positive electrode material region. p The difference is 100mm-220mm.
[0016] Furthermore, under the initial conditions of 25°C and 4.0V, the discharge time of the cylindrical lithium-ion battery from 200W constant power to 2.5V is not less than 170s, and the discharge time from 220W constant power to 2.5V is not less than 150s. Preferably, at 25°C and a voltage window of 4.2V-2.5V, the cylindrical lithium-ion battery retains a capacity of not less than 78% after 1000 cycles of charging at 8A and discharging at 50A, or a capacity of not less than 80% after 1000 cycles of charging at 14A and discharging at 40A. Preferably, the cylindrical lithium-ion battery has a DCR of no more than 8.0 mΩ at 25°C and 100% SOC, and an overpotential of no more than 0.30V under discharge conditions of 25°C and 50A. Preferably, the highest surface temperature of the cylindrical lithium-ion battery when discharged at 40A, 50A and 60A at 25°C and 100% SOC is no higher than 60°C, 68°C and 73°C, respectively.
[0017] Secondly, a method for preparing a cylindrical lithium-ion battery according to any one of the above claims includes the following steps: A positive electrode, a separator, and a negative electrode are wound together to form a wound electrode assembly. The wound electrode assembly is then placed into a housing and injected with electrolyte. After formation, aging, and capacity testing, the cylindrical lithium-ion battery is obtained.
[0018] Thirdly, the application of any of the above-mentioned cylindrical lithium-ion batteries in battery modules, battery packs, or electrical devices.
[0019] Compared with the prior art, the present invention has at least the following beneficial effects: The cylindrical lithium-ion battery provided by this invention, on the one hand, increases the single-sided active area of the positive electrode while reducing the equivalent areal capacity and bi-sided equivalent areal current density, thus reducing polarization and temperature rise under 40A, 50A, and 60A discharge, while maintaining a capacity of approximately 4Ah. On the other hand, the length and width of the negative electrode material region are relatively extended outward compared to the positive electrode material region, allowing the long electrode winding structure to maintain good negative electrode bearing capacity at the ends and edges. Simultaneously, combined with a high-nickel layered positive electrode, a composite negative electrode of artificial graphite and silicon-carbon materials, a moderate N / P value, and a thin negative electrode current collector, it can effectively improve constant power discharge time and high-rate cycle capacity retention without sacrificing the 4Ah capacity, resulting in lower rate polarization and more stable cycle performance. In summary, this invention achieves the technical effects of improving high-rate discharge, constant power output, and high-rate cycle performance through the coordinated design of material region length, active area, equivalent areal capacity, areal current density, relative negative electrode length, and material system. Detailed Implementation
[0020] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] According to a first aspect of the present invention, a cylindrical lithium-ion battery is provided, comprising a wound electrode assembly, a housing, and an electrolyte. The wound electrode assembly includes a positive electrode, a negative electrode, and a separator disposed between the positive and negative electrode. The positive electrode includes a positive current collector and a positive active material layer disposed on the surface of the positive current collector. The negative electrode includes a negative current collector and a negative active material layer disposed on the surface of the negative current collector. The equivalent positive electrode areal capacity Q of the cylindrical lithium-ion battery is... p 1.80mAh / cm 2 -2.25mAh / cm 2 ; The equivalent positive electrode current density J of this cylindrical lithium-ion battery during 40A discharge is... 40 18mA / cm 2 -22.04mA / cm 2 The double-sided equivalent positive electrode current density J during 50A discharge. 50 22mA / cm 2 -27.55mA / cm 2 The double-sided equivalent positive electrode current density J during 60A discharge. 60 27mA / cm 2 -33.06mA / cm2 ; The positive electrode (active material layer) material area of this cylindrical lithium-ion battery has a length L. p The width W of the positive electrode (active material layer) material area is 1500mm-1850mm. p The length L of the negative electrode (active material layer) material area is 59mm-62mm. n Greater than the length L of the positive electrode material region p The width W of the negative electrode (active material layer) material area n Width greater than the positive electrode material region W p ; The positive electrode active material in the positive electrode region includes high-nickel layered lithium transition metal oxide; The negative electrode active materials in the negative electrode material region include artificial graphite and silicon carbide materials; The equivalent negative electrode surface capacity Q of this cylindrical lithium-ion battery n With equivalent positive electrode surface capacity Q p The ratio N / P is 1.02-1.09.
[0022] The advantages of the cylindrical lithium-ion battery of this invention are as follows: On the one hand, under the premise of a capacity of approximately 4Ah, the active area on one side of the positive electrode is increased, and the equivalent surface capacity and the equivalent surface current density on both sides are reduced, thereby reducing polarization and temperature rise under discharge at 40A, 50A and 60A; on the other hand, the length and width of the negative electrode material area are relatively expanded outward compared with the positive electrode material area, so that the long electrode winding structure maintains good negative electrode bearing capacity at the ends and edges; at the same time, with the high-nickel layered positive electrode, the composite negative electrode of artificial graphite and silicon-carbon material, the appropriate N / P value and the thin current collector of the negative electrode, the constant power discharge time and high rate cycle capacity retention rate can be effectively improved without sacrificing the 4Ah level capacity, with lower rate polarization and more stable cycle performance.
[0023] In summary, this invention achieves the technical effect of improving high-rate discharge, constant power output, and high-rate cycling performance by coordinating the design of material zone length, active area, equivalent areal capacity, areal current density, relative length of negative electrode, and material system.
[0024] In a preferred embodiment, the discharge capacity C of the cylindrical lithium-ion battery when discharged from 0.2C to 2.5V can be 3800mAh-4300mAh.
[0025] In a preferred embodiment, the cylindrical lithium-ion battery has a maximum surface temperature of no more than 78°C when discharged at 60A at 25°C and 100% SOC, and a capacity retention rate of no less than 88% after 600 cycles of charging at 8A and discharging at 40A at 25°C.
[0026] In a preferred embodiment, the length L of the positive electrode material region is... pThe width W of the positive electrode material area can be 1700mm-1800mm. p It can be 60mm-61mm, through the design of long electrode structure, the single-sided active area S of the positive electrode p It can reach 900cm 2 -1120cm 2 It can be further increased to 1020cm 2 -1100cm 2 .
[0027] After increasing the length of the positive electrode material region to 1700mm to 1800mm, the single-sided active area S of the positive electrode... p With the synchronous increase, the discharge current of 40A to 60A is distributed over a larger double-sided reaction area, which reduces the surface current density. This is beneficial for reducing the lithium delithiation flux on the surface of the positive electrode particles, and for reducing the concentration gradient and liquid phase ohmic voltage drop in the electrolyte. This is manifested as a decrease in temperature rise at 60A and an increase in cycle retention rate at 8A / 40A.
[0028] In a preferred embodiment, the length L of the negative electrode material region is... n Comparable cathode material region length L p Large 30mm-90mm, negative electrode material area width W n Comparable cathode material region width W p With a diameter of 1mm-3mm, the negative electrode covers the active region of the positive electrode in both the length and width directions, which can reduce the risk of local lithium plating at the beginning, end and edge positions of the long electrode winding structure.
[0029] The difference between the length of the negative electrode material area and the length of the positive electrode material area will affect the lithium-ion receiving boundary of the winding head and tail areas. If the difference is too low, the winding tension fluctuation, electrode thermal shrinkage or assembly misalignment may cause the local positive electrode area to lack sufficient negative electrode capacity to receive, which will increase the risk of edge lithium plating and amplify capacity decay in high-rate charge and discharge cycles.
[0030] In a preferred embodiment, the single-sided active area S of the negative electrode n With positive electrode single-sided active area S p The ratio can be 1.03-1.12.
[0031] In a preferred embodiment, the equivalent positive electrode surface capacity Q p It can reach 1.86mAh / cm 2 -2.05mAh / cm 2 .
[0032] The length of the material zone is related to the equivalent positive electrode surface capacity Q. p and the double-sided equivalent positive electrode current density J 40 J 50 J 60The shared limitation allows the same capacity and the same discharge current to be distributed over a larger reaction area, thereby reducing the reaction flux and polarization heat at the positive and negative electrode interfaces.
[0033] Equivalent negative electrode surface capacity Q n With equivalent positive electrode surface capacity Q p A N / P ratio in the range of 1.02-1.09 can provide adequate capacity redundancy for lithium intercalation in the negative electrode during high-rate charging and avoid excessively low local potential in the negative electrode. If the N / P ratio is too low, the reversible capacity of the negative electrode will be insufficient, and the head, tail, or adjacent areas of the tab will be more likely to approach a fully intercalated state during high-rate cycling, which will increase the risk of lithium plating and impedance growth. If the N / P ratio is too high, it will result in ineffective mass and increase the thickness of the core.
[0034] In this invention, the positive electrode active material layer includes high-nickel lithium nickel cobalt manganese oxide and / or high-nickel lithium nickel cobalt aluminum oxide, lithium carbonate, carbon black, and polyvinylidene fluoride.
[0035] In a preferred embodiment, based on transition metal elements, the molar percentage of nickel in the high-nickel layered lithium transition metal oxide can be 80%-93%.
[0036] In a preferred embodiment, the areal density of the positive electrode sheet on one side can be 9.8 mg / cm³. 2 -11.3mg / cm 2 It can be further preferred to be 10.2 mg / cm³. 2 -10.9mg / cm 2 The compaction density of the positive electrode sheet can be 3.40 g / cm³. 3 -3.60g / cm 3 It can be further optimized to be 3.45 g / cm³. 3 -3.55g / cm 3 .
[0037] In this invention, the negative electrode active material layer includes artificial graphite, silicon-containing active phase and carbon-based skeleton silicon-carbon material, carbon black, carboxymethyl cellulose and styrene-butadiene rubber; wherein the mass percentage of silicon-carbon material can be 3%-10%.
[0038] In a preferred embodiment, the areal density of the negative electrode sheet on one side can be 4.7 mg / cm³. 2 -5.8mg / cm 2 Meanwhile, the compaction density of the negative electrode sheet can be 1.42 g / cm³. 3 -1.58g / cm 3 .
[0039] In a preferred embodiment, the negative electrode current collector can be copper foil, and the thickness of the negative electrode current collector can be 5μm-7μm, which is beneficial to release the radial space of the core and keep the length of the positive and negative electrode material areas within the range of long electrode sheets; if the thickness of the negative electrode current collector is too large, the space available for the active coating, separator and winding allowance in the same housing space will be compressed, which is not conducive to increasing the single-sided active area of the positive electrode.
[0040] In a preferred embodiment, the electrolyte used in the cylindrical lithium-ion battery includes, but is not limited to, lithium salts, organic solvents, and additives. The composition of the electrolyte affects the silicon-carbon anode interface film, the high-potential side reaction of the cathode, and the impedance increase after high-temperature storage. The lithium salt can be selected from lithium hexafluorophosphate, and the organic solvent includes, but is not limited to, at least one of cyclic carbonates, chain carbonates, and low-viscosity cosolvents such as acetates. The additives include, but are not limited to, at least one of lithium difluorophosphate additives, fluorocarbonate film-forming additives, sulfonate lactone additives, and boron-containing lithium salt additives.
[0041] Based on the total mass of the electrolyte, the mass percentage of low-viscosity co-solvents such as acetates in the electrolyte can be 0-15.0%, the mass percentage of film-forming additives such as fluorocarbonates can be 2.0%-2.5%, and the mass percentage of lithium difluorophosphate additives can be 0.5%-1.0%. This is beneficial for high-temperature storage recovery and partial improvement of high-temperature cycling performance. If lithium difluorophosphate additives are not added and the low-viscosity co-solvents such as acetates are too high, it will lead to poor interfacial film stability and gas generation control.
[0042] The specific material system in this invention, combined with low areal capacity, low areal current density, and moderate N / P value, enables a cylindrical lithium-ion battery with a capacity of 4Ah to maintain capacity, polarization, and thermal stability during high-rate cycling.
[0043] In a preferred embodiment, the separator width in the cylindrical lithium-ion battery is greater than the width W of the negative electrode material region. n The diaphragm width can be 63.5mm-66.5mm; the diaphragm length is greater than the length L of the negative electrode material region. n .
[0044] In a preferred embodiment, the separator length is related to the positive electrode material region length L. p The difference can be 100mm-220mm.
[0045] The core structural parameters of the cylindrical lithium-ion battery of this invention can be obtained through finished product disassembly, size measurement, capacity testing, weighing and material characterization, which is beneficial for product testing and judgment.
[0046] In a preferred embodiment, at an initial state of 25°C and 4.0V, the cylindrical lithium-ion battery of the present invention has a discharge time of not less than 170s when discharged to 2.5V at a constant power of 200W, and a discharge time of not less than 150s when discharged to 2.5V at a constant power of 220W.
[0047] In a preferred embodiment, at 25°C and a voltage window of 4.2V-2.5V, the capacity retention rate of the cylindrical lithium-ion battery of the present invention after 1000 cycles of charging at 8A and discharging at 50A is not less than 78%, or after 1000 cycles of charging at 14A and discharging at 40A is not less than 80%.
[0048] In a preferred embodiment, the cylindrical lithium-ion battery of the present invention has a DCR of no more than 8.0 mΩ at 25°C and 100% SOC, and an overpotential of no more than 0.30 V under discharge conditions of 25°C and 50A.
[0049] In a preferred embodiment, the highest surface temperature of the cylindrical lithium-ion battery of the present invention when discharged at 40A, 50A and 60A at 25°C and 100% SOC is no higher than 60°C, 68°C and 73°C, respectively.
[0050] According to a second aspect of the present invention, a method for preparing a cylindrical lithium-ion battery as described in any one of the preceding claims is provided, comprising the following steps: A positive electrode, a separator, and a negative electrode are wound together to form a wound electrode assembly. The wound electrode assembly is then placed into a housing and injected with electrolyte. After formation, aging, and capacity testing, a cylindrical lithium-ion battery is obtained.
[0051] In this invention, a positive electrode slurry is coated onto a positive electrode current collector, and after drying, rolling and slitting, a positive electrode sheet is obtained; a negative electrode slurry is coated onto a negative electrode current collector (such as copper foil), and after drying, rolling and slitting, a negative electrode sheet is obtained; the positive electrode sheet, the separator and the negative electrode sheet are wound together to form a wound electrode assembly; the wound electrode assembly is installed into a housing and then injected with electrolyte, and after formation, aging and capacity testing, a cylindrical lithium-ion battery is obtained.
[0052] According to a third aspect of the present invention, an application of the cylindrical lithium-ion battery described in any of the preceding claims in a battery module, battery pack, or electrical device is provided.
[0053] The present invention will be further illustrated by the following examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or purchased directly from the market.
[0054] The material zone length refers to the length of the active material layer continuously coated along the winding direction after the electrode sheet is unfolded, excluding the uncoated tab area, the welding blank area, and the trimmed burrs; the material zone width refers to the width of the active material coating perpendicular to the winding direction after the electrode sheet is unfolded.
[0055] The single-sided active area S of the positive electrode active material layer p Calculate S using the following formula: p =L p ×W p / 100; where L p W represents the length of the positive electrode active material layer in mm. p S represents the width of the positive electrode active material layer, in mm. p The unit is cm 2 .
[0056] Equivalent positive electrode surface capacity Q p Calculate Q using the following formula: p =C / (2S p In the formula, C is the discharge capacity of the cylindrical lithium-ion battery when discharged from 0.2C to 2.5V, in mAh; Q p The unit is mAh / cm 2 .
[0057] Equivalent negative electrode surface capacity Q n Calculate Q using the following formula: n =M n ×C n / 1000; where M n The surface density of the negative electrode is expressed in mg / cm³. 2 C n The reversible capacity of the negative electrode active material layer is obtained by measuring its gram capacity, and the unit is mAh / g.
[0058] Double-sided equivalent positive electrode current density J I Calculate J using the following formula: I =I×1000 / (2S p In the formula, I is the discharge current, in amperes (A); J I The unit is mA / cm 2 Correspondingly, J 40 =40000 / (2S p ), J 50 =50000 / (2S p ), J 60 =60000 / (2S p ).
[0059] The ratio of negative electrode capacity to positive electrode capacity, N / P, is calculated using the following formula: η N / P =Q n / Qp In the formula, Q n Q is the equivalent negative electrode surface capacity. p This represents the equivalent positive electrode surface capacity.
[0060] Capacity C test: The cylindrical lithium-ion battery was placed in an environment of 25±2℃ and left to stand for 2 hours. It was then charged at a constant current of 0.2C to 4.2V, followed by constant voltage charging to the cutoff current of 0.05C, and left to stand for 10 minutes. Subsequently, it was discharged at a constant current of 0.2C to 2.5V, and the discharge capacity was recorded. This test was repeated three times, and the discharge capacity of the third test was taken as the capacity C, in mAh.
[0061] Material zone length and width tests: After capacity testing, the battery was discharged to 2.5V and disassembled in an environment with a dew point no higher than -40℃. The wound electrode assembly was removed, and the positive and negative electrode sheets were unfolded. The residual electrolyte on the electrode surface was cleaned with anhydrous dimethyl carbonate, and the electrodes were vacuum dried at 60℃ for 2 hours. The length of the continuously coated active material layer along the winding direction was measured using an image measuring instrument as the material zone length L. p or L n The coating width perpendicular to the winding direction is measured as the material area width W. p or W n Each parameter was measured once at the beginning, middle and end of the electrode, and the arithmetic mean was taken, accurate to 0.1 mm.
[0062] Areal density, compacted density, and current collector thickness testing: A 100.00cm² area was cut from the center of the unfolded electrode sheet. 2 Three sample pieces were prepared, and their total mass was measured. The active material layer on both sides of each sample was removed with a scraper, and the mass of the current collector was then measured. The surface density of one side was calculated using the following formula: M = (m1 - m0) / (2A); where M is the surface density of one side, in mg / cm³. 2 m1 is the total mass of the sample before the active material layer is removed, in mg; m0 is the mass of the current collector after the active material layer is removed, in mg; A is the area of one side of the sample, in cm². 2 Take the arithmetic mean of the three sample pieces.
[0063] The thickness of the active material layer and the current collector thickness were measured using a cross-sectional scanning electron microscope. Measurements were taken at five locations on each sample, and the arithmetic mean was used. The compaction density was calculated using the following formula: ρ = M / t × 10; where ρ is the compaction density, in g / cm³. 3 M is the surface density of a single surface, in mg / cm³. 2 t represents the thickness of the single-sided active material layer, in μm.
[0064] Material composition testing: The layered structure of the positive electrode active material was confirmed by X-ray diffraction; the content of transition metal elements in the positive electrode active material was determined by inductively coupled plasma atomic emission spectrometry, and the molar percentage of nickel was calculated by dividing the molar amount of nickel by the sum of the molar amounts of all transition metal elements in nickel, cobalt, manganese, and aluminum; the composition of artificial graphite and silicon-carbon materials in the negative electrode was confirmed by Raman spectroscopy, scanning electron microscopy-energy dispersive spectroscopy, and thermogravimetric analysis, and the mass percentage of silicon-carbon materials was calculated based on the silicon content and corrected for thermogravimetric residual content.
[0065] Electrolyte composition testing: After discharging the battery to 2.5V, disassemble it in an environment with a dew point not higher than -40℃, and collect the free electrolyte by centrifugation; lithium salt anions and lithium difluorophosphate additives were tested by ion chromatography; organic solvents, low-viscosity co-solvents such as acetates, fluorocarbonate film-forming additives, vinylene carbonate additives, and sulfonate lactone additives were tested by gas chromatography-mass spectrometry; the mass percentage of each component was calculated by dividing the quantitative result of the external standard method by the total mass of the electrolyte.
[0066] Example 1 A method for preparing a cylindrical lithium-ion battery includes the following steps: (1) Preparation of positive electrode slurry: Based on the mass fractions of solid components, 96.5 parts of high-nickel lithium nickel cobalt manganese oxide cathode active material, 1.0 part of lithium carbonate, 1.2 parts of carbon black, and 1.3 parts of polyvinylidene fluoride were taken; wherein, nickel accounted for 90% of the molar percentage of transition metal elements in the cathode active material. First, polyvinylidene fluoride is added to N-methylpyrrolidone and stirred to dissolve. Then, carbon black is added to disperse it. Subsequently, high-nickel lithium nickel cobalt manganese oxide positive electrode active material and lithium carbonate are added and stirred continuously. The solid content of the slurry is adjusted to 67% to obtain the positive electrode slurry. (2) Preparation of negative electrode slurry: Based on the mass percentage of solid components (silicon-carbon materials accounting for 6.0%), take 90.9 parts of artificial graphite, 6.0 parts of silicon-carbon materials containing silicon active phase and carbon-based skeleton, 0.4 parts of carbon black, 1.2 parts of carboxymethyl cellulose and 1.5 parts of styrene-butadiene rubber; First, carboxymethyl cellulose is dissolved in deionized water, then artificial graphite, silicon carbide and carbon black are added and dispersed, and finally styrene-butadiene rubber is added and stirred to adjust the solid content of the slurry to 50% to obtain the negative electrode slurry. (3) Selection of diaphragm and electrolyte: The separator is made of polyolefin porous base membrane and has a ceramic coating on at least one side; the separator width is 65mm, the separator length is greater than the length of the negative electrode material area, and the separator covers the edge areas of the positive electrode material area and the negative electrode material area; The electrolyte includes 1.0 mol / L lithium hexafluorophosphate, ethyl acetate, fluoroethylene carbonate, vinylene carbonate, lithium difluorophosphate, and 1,3-propanesulfonate lactone. Based on the total mass of the electrolyte, ethyl acetate accounts for 15.0%, fluoroethylene carbonate accounts for 2.0%, vinylene carbonate accounts for 1.0%, lithium difluorophosphate accounts for 0.5%, and 1,3-propanesulfonate lactone accounts for 0.5%. (4) Preparation of positive and negative electrode plates: The positive electrode slurry was coated on both sides of a 12μm thick aluminum foil, and then dried in multiple stages with the temperature gradually increased from 90℃ to 120℃ (to gradually remove the solvent from the coating and avoid surface drying leading to inner layer residue), rolled, and slit to obtain the positive electrode sheet; wherein the rolling was performed with a positive electrode compaction density of 3.50 g / cm³. 3 As a control result, the length L of the positive electrode material region after slitting... p 1750mm, material zone width W p It has a diameter of 60.5 mm and a single-sided areal density of 10.57 mg / cm³. 2 ; The negative electrode slurry was coated on both sides of a 6.0 μm thick copper foil, and then dried in multiple stages with the temperature gradually increased from 80℃ to 110℃, followed by rolling and slitting to obtain the negative electrode sheet; wherein the rolling was performed to achieve a negative electrode compaction density of 1.50 g / cm³. 3 As a control result, the length L of the negative electrode material region after slitting... n 1805mm, material zone width W n The diameter is 62.5 mm, and the surface density of the negative electrode is 5.20 mg / cm³. 2 ; (5) Winding, assembly, liquid injection, formation and volume division: The positive electrode, separator, and negative electrode are wound into a wound electrode assembly with the negative electrode covering the positive electrode in both the length and width directions, and the winding tension is 0.50N. The wound electrode assembly is then installed into a cylindrical shell, and the current collector connection, sealing, and baking are completed. After the electrolyte is injected, the battery is allowed to stand, form, age, and be tested for capacity to obtain a cylindrical lithium-ion battery. The single-sided active area S of the positive electrode active material layer p =1750×60.5 / 100=1058.75cm 2 Equivalent positive electrode surface capacity Q p =4104 / (2×1058.75)=1.94mAh / cm 2 The double-sided equivalent positive electrode current density J during 40A discharge. 40 =40000 / (2×1058.75)=18.89mA / cm 2The double-sided equivalent positive electrode current density J during 50A discharge. 50 =50000 / (2×1058.75)=23.61mA / cm 2 The double-sided equivalent positive electrode current density J during 60A discharge. 60 =60000 / (2×1058.75)=28.34mA / cm 2 Equivalent negative electrode surface capacity Q n 2.04mAh / cm 2 Equivalent negative electrode surface capacity Q n With equivalent positive electrode surface capacity Q p The ratio N / P is 1.05.
[0067] Example 2 The difference between this embodiment and Embodiment 1 is that, in step (4), the length L of the positive electrode material region... p The diameter was changed from 1750mm to 1500mm, and the surface density of the positive electrode was 12.26 mg / cm³. 2 The surface density of the negative electrode is 6.02 mg / cm³. 2 The positive electrode single-sided active area S p From 1058.75cm 2 It became 907.50cm 2 ; Everything else is the same as in Example 1.
[0068] Example 3 The difference between this embodiment and Embodiment 1 is that, in step (4), the length L of the positive electrode material region... p The diameter was changed from 1750mm to 1600mm, and the surface density of the positive electrode was 11.54 mg / cm³. 2 The surface density of the negative electrode is 5.67 mg / cm³. 2 The positive electrode single-sided active area S p From 1058.75cm 2 It became 968.00cm 2 ; Everything else is the same as in Example 1.
[0069] Example 4 The difference between this embodiment and Embodiment 1 is that, in step (4), the length L of the positive electrode material region... p The diameter was changed from 1750mm to 1700mm, and the surface density of the positive electrode was 10.86 mg / cm³. 2 The surface density of the negative electrode is 5.33 mg / cm³. 2 The positive electrode single-sided active area S p From 1058.75cm 2 It became 1028.50cm 2; Everything else is the same as in Example 1.
[0070] Example 5 The difference between this embodiment and Embodiment 1 is that, in step (4), the length L of the positive electrode material region... p The diameter was changed from 1750mm to 1800mm, and the surface density of the positive electrode was 10.26 mg / cm³. 2 The surface density of the negative electrode is 5.04 mg / cm³. 2 The positive electrode single-sided active area S p From 1058.75cm 2 It became 1089.00cm 2 Length L of the negative electrode material region n It is 1900mm; Everything else is the same as in Example 1.
[0071] Example 6 The difference between this embodiment and Embodiment 1 is that, in step (4), the length L of the positive electrode material region... p The width W of the positive electrode material area changed from 1750mm to 1850mm. p The diameter was changed from 60.5mm to 59.5mm, and the single-sided active area S of the positive electrode was... p From 1058.75cm 2 It became 1100.75cm 2 Length L of the negative electrode material region n It is 1900mm; Everything else is the same as in Example 1.
[0072] Example 7 The difference between this embodiment and embodiment 1 is that, in step (4), the width W of the positive electrode material region... p The diameter was changed from 60.5 mm to 59 mm, and the areal density of the positive electrode on one side was 10.82 mg / cm³. 2 The surface density of the negative electrode is 5.31 mg / cm³. 2 The positive electrode single-sided active area S p From 1058.75cm 2 It becomes 1032.50cm 2 ; Everything else is the same as in Example 1.
[0073] Example 8 The difference between this embodiment and embodiment 1 is that, in step (4), the width W of the positive electrode material region... p The diameter was changed from 60.5 mm to 61 mm, and the areal density of the positive electrode on one side was 10.46 mg / cm³. 2 The surface density of the negative electrode is 5.14 mg / cm³. 2 The positive electrode single-sided active area Sp From 1058.75cm 2 It became 1067.50cm 2 ; Everything else is the same as in Example 1.
[0074] Example 9 The difference between this embodiment and embodiment 1 is that, in step (4), the width W of the positive electrode material region... p The diameter was changed from 60.5mm to 62mm, and the areal density of the positive electrode on one side was 10.29mg / cm³. 2 The surface density of the negative electrode is 5.06 mg / cm³. 2 The positive electrode single-sided active area S p From 1058.75cm 2 It becomes 1085.00cm 2 ; Everything else is the same as in Example 1.
[0075] Example 10 The difference between this embodiment and Embodiment 1 is that, in step (4), the surface density of the negative electrode is 5.05 mg / cm³. 2 The negative electrode compaction density is 1.46 g / cm³. 3 Equivalent negative electrode surface capacity Q n From 2.04mAh / cm 2 It became 1.98mAh / cm 2 Equivalent negative electrode surface capacity Q n With equivalent positive electrode surface capacity Q p The ratio N / P changed from 1.05 to 1.02; Everything else is the same as in Example 1.
[0076] Example 11 The difference between this embodiment and Embodiment 1 is that, in step (4), the surface density of the negative electrode is 5.38 mg / cm³. 2 The negative electrode compaction density is 1.55 g / cm³. 3 Equivalent negative electrode surface capacity Q n From 2.04mAh / cm 2 It became 2.11mAh / cm 2 Equivalent negative electrode surface capacity Q n With equivalent positive electrode surface capacity Q p The ratio N / P changed from 1.05 to 1.09; Everything else is the same as in Example 1.
[0077] Example 12 The difference between this embodiment and Embodiment 1 is that, in step (4), the length L of the positive electrode material region... pThe length L of the negative electrode material region was changed from 1750mm to 1700mm. n The diameter of the cathode decreased from 1805 mm to 1755 mm; the single-sided active area of the positive electrode, S... p From 1058.75cm 2 It became 1028.50cm 2 ; Everything else is the same as in Example 1.
[0078] Example 13 The difference between this embodiment and Embodiment 1 is that, in step (4), the length L of the positive electrode material region... p The length L of the negative electrode material region changed from 1750mm to 1800mm. n The diameter of the cathode changed from 1805mm to 1855mm; the single-sided active area of the positive electrode, S p From 1058.75cm 2 It became 1089.00cm 2 ; Everything else is the same as in Example 1.
[0079] Example 14 The difference between this embodiment and Embodiment 1 is that, in step (4), the length L of the negative electrode material region is... n The diameter of the tube was changed from 1805mm to 1790mm. Everything else is the same as in Example 1.
[0080] Example 15 The difference between this embodiment and Embodiment 1 is that, in step (4), the surface density of the positive electrode single side is changed from 10.57 mg / cm³. 2 It became 10.25 mg / cm³ 2 Equivalent positive electrode surface capacity Q p From 1.94mAh / cm 2 It became 1.88mAh / cm 2 ; Everything else is the same as in Example 1.
[0081] Example 16 The difference between this embodiment and Embodiment 1 is that, in step (4), the surface density of the positive electrode single side is changed from 10.57 mg / cm³. 2 It became 10.90 mg / cm³ 2 Equivalent positive electrode surface capacity Q p From 1.94mAh / cm 2 It becomes 2.00mAh / cm 2 ; Everything else is the same as in Example 1.
[0082] Example 17 The difference between this embodiment and Embodiment 1 is that, in step (4), the surface density of the negative electrode is 5.30 mg / cm³. 2 The negative electrode compaction density is 1.52 g / cm³. 3 Equivalent negative electrode surface capacity Q n From 2.04mAh / cm 2 It became 2.08mAh / cm 2 Equivalent negative electrode surface capacity Q n With equivalent positive electrode surface capacity Q p The ratio N / P changed from 1.05 to 1.07; Everything else is the same as in Example 1.
[0083] Example 18 The difference between this embodiment and Embodiment 1 is that the silicon-carbon material accounts for 5.0% of the mass of the negative electrode material, and the areal density of the negative electrode on one side is 5.35 mg / cm³. 2 ; Everything else is the same as in Example 1.
[0084] Example 19 The difference between this embodiment and embodiment 1 is that, in step (4), the thickness of the copper foil (negative electrode current collector) is changed from 6.0 μm to 5.5 μm; Everything else is the same as in Example 1.
[0085] Example 20 The difference between this embodiment and Embodiment 1 is that, in step (3), the mass percentage of ethyl acetate in the electrolyte changes from 15.0% to 10.0%, and the mass percentage of lithium difluorophosphate changes from 0.5% to 1.0%. Everything else is the same as in Example 1.
[0086] Example 21 The difference between this embodiment and Example 1 is that, in step (3), the mass percentage of ethyl acetate in the electrolyte changes from 15.0% to 0%, the mass percentage of fluoroethylene carbonate changes from 2.0% to 2.5%, and the mass percentage of lithium difluorophosphate changes from 0.5% to 1.0%. Everything else is the same as in Example 1.
[0087] Example 22 The difference between this embodiment and Embodiment 1 is that, in step (4), the length L of the negative electrode material region is... n The diameter of the tube was changed from 1805mm to 1755mm. Everything else is the same as in Example 1.
[0088] Example 23 The difference between this embodiment and Embodiment 1 is that the silicon-carbon material accounts for 1.0% of the mass of the negative electrode material, and the areal density of the negative electrode is 6.20 mg / cm³. 2 ; Everything else is the same as in Example 1.
[0089] Example 24 The difference between this embodiment and Embodiment 1 is that, in step (4), the thickness of the copper foil (negative electrode current collector) changes from 6.0 μm to 8.0 μm, and the length L of the positive electrode material region... p The diameter of the positive electrode is changed from 1750mm to 1600mm, and the single-sided active area S is reduced. p From 1058.75cm 2 It became 968.00cm 2 ; Everything else is the same as in Example 1.
[0090] Example 25 The difference between this embodiment and Embodiment 1 is that, in step (3), the mass percentage of lithium difluorophosphate additives in the electrolyte changes from 0.5% to 0%, and the mass percentage of low-viscosity co-solvents such as acetate changes from 15.0% to 35.0%. Everything else is the same as in Example 1.
[0091] Comparative Example 1 The difference between this comparative example and Example 1 is that, in step (4), the length L of the positive electrode material region is... p The length L of the negative electrode material region was changed from 1750mm to 1348mm. n The diameter of the cathode decreased from 1805 mm to 1401 mm; the single-sided active area of the positive electrode, S... p From 1058.75cm 2 It became 815.54cm 2 ; Everything else is the same as in Example 1.
[0092] Comparative Example 2 The difference between this comparative example and Example 1 is that, in step (4), the length L of the positive electrode material region is... p The length L of the negative electrode material region was changed from 1750mm to 1450mm. n The diameter of the cathode was changed from 1805 mm to 1505 mm; the single-sided active area of the positive electrode, S p From 1058.75cm 2 It became 877.25cm 2 ; Everything else is the same as in Example 1.
[0093] Comparative Example 3 The difference between this comparative example and Example 1 is that, in step (4), the length L of the positive electrode material region is... pThe diameter of the cathode increased from 1750 mm to 1880 mm; the single-sided active area of the positive electrode, S... p From 1058.75cm 2 It became 1137.40cm 2 ; Everything else is the same as in Example 1.
[0094] Comparative Example 4 The difference between this comparative example and Example 1 is that, in step (4), the length L of the positive electrode material region is... p The diameter of the cathode decreased from 1750 mm to 1475 mm, and the surface density of the cathode increased from 10.57 mg / cm³. 2 It changed to 12.30 mg / cm³ 2 Positive electrode single-sided active area S p From 1058.75cm 2 It became 892.38cm 2 Equivalent positive electrode surface capacity Q p From 1.94mAh / cm 2 It became 2.30mAh / cm 2 ; Everything else is the same as in Example 1.
[0095] Comparative Example 5 The difference between this comparative example and Example 1 is that, in step (4), the areal density of the negative electrode single side is 5.54 mg / cm³. 2 The negative electrode compaction density is 1.59 g / cm³. 3 Equivalent negative electrode surface capacity Q n 2.17mAh / cm 2 Equivalent negative electrode surface capacity Q n With equivalent positive electrode surface capacity Q p The ratio N / P changed from 1.05 to 1.12; Everything else is the same as in Example 1.
[0096] Comparative Example 6 The difference between this comparative example and Example 1 is that, in step (4), the areal density of the negative electrode is 4.80 mg / cm³. 2 The negative electrode compaction density is 1.45 g / cm³. 3 Equivalent negative electrode surface capacity Q n From 2.04mAh / cm 2 It became 1.90mAh / cm 2 Equivalent negative electrode surface capacity Q n With equivalent positive electrode surface capacity Q p The ratio N / P changed from 1.05 to 0.98; Everything else is the same as in Example 1.
[0097] Table 1 summarizes the structural parameters of the cylindrical lithium-ion batteries in each embodiment and comparative example.
[0098] Table 1
[0099] Test case The cylindrical lithium-ion batteries of each embodiment and comparative example were subjected to performance tests, and the performance results are shown in Tables 2, 3 and 4, respectively.
[0100] The performance testing items and methods are as follows: Capacity test: The battery under test is placed in an environment of 25±2℃ for no less than 2 hours, charged at a constant current of 0.2C to 4.2V, then charged at a constant voltage until the cutoff current is no greater than 0.05C, placed in a place for 30 minutes, and then discharged at a constant current of 0.2C to 2.5V. The discharge capacity C is recorded. The test is repeated 3 times, and the discharge capacity of the 3rd test is taken as the capacity result. ACR and DCR tests: AC internal resistance (ACR) was tested at 25±2℃ and near 3.95V using a 1kHz AC internal resistance meter; for DCR testing, the battery was adjusted to 100% SOC and left to stand at the target temperature for 60 minutes, and the pre-pulse voltage V0 was recorded to set the discharge current I. p Discharge for 10 seconds, record the voltage V at the 10th second. 10 DCR is calculated using the following formula: DCR = (V0 - V 10 ) / I p ×1000, where DCR is in mΩ, I p The unit is A; Rate discharge temperature rise test: The battery under test was charged to 100% SOC at 25±2℃ and left to stand for at least 2 hours. The surface temperature of the casing was recorded using a patch thermocouple. The temperature measuring point was set at 1 / 2±2mm of the axial height of the casing, avoiding the heat-affected zone of the weld seam and the tab welding. The battery was discharged to 2.5V at a constant current of 40A, 50A and 60A respectively. The highest surface temperature T was recorded within 300s from the start of discharge to the end of discharge. max ; High-rate cycling test: The battery under test is subjected to high-rate cycling in an environment of 25±2℃; the 8A / 40A cycle mode is as follows: charge at a constant current of 8A to 4.2V, then charge at a constant voltage until the cutoff current is no greater than 0.2A, and let it stand for 10 minutes; discharge at a constant current of 40A to 2.5V, and let it stand for 10 minutes, which is recorded as 1 cycle; in the 8A / 50A and 8A / 60A modes, the discharge current is replaced with 50A and 60A respectively; in the 14A / 30A, 14A / 40A and 14A / 50A modes, the charging current is replaced with 14A, and the discharge currents are 30A, 40A and 50A respectively; the capacity retention rate R is calculated by the following formula, R=C n / C1×100%, where Cn C1 is the discharge capacity of the nth cycle, and C2 is the discharge capacity of the 1st cycle. 35℃ / 45℃ Constant Power Cyclic Test: Place the battery under test in an environment of 35±2℃ or 45±2℃, charge it to 4.0V at 4A and keep the voltage constant until the cutoff current is no more than 0.2A, let it stand for 10 minutes, then discharge it to 2.5V at a constant power of 200W or 220W, let it stand for 10 minutes, and record this as one cycle; record the capacity retention rate, discharge time and whether any abnormal protection occurs during the test; 200W / 220W constant power discharge test: Adjust the battery under test to an initial voltage of 4.0V, and let it stand for no less than 2 hours in an environment of 25℃, 35℃ or 45℃. Discharge it to 2.5V with a constant power of 200W or 220W, and record the discharge time. The termination condition is that the cell terminal voltage reaches 2.5V or the test equipment triggers the safety protection, whichever comes first.
[0101] Table 2
[0102] Table 3
[0103] Table 4
[0104] Comparing the cylindrical lithium-ion battery structural parameters and performance data of Examples 1, 12, and 13 with Comparative Examples 1 and 2, it can be seen that after increasing the length of the positive electrode material region from a shorter electrode sheet to 1700 mm to 1800 mm, the single-sided active area S of the positive electrode increases. p With the synchronous increase, the 40A to 60A discharge current is distributed over a larger double-sided reaction area, making J 60 From Comparative Example 1, approximately 36.79 mA / cm 2 Reduced to approximately 28.34 mA / cm² in Example 1. 2 When the surface current density decreases, the lithium delithiation flux on the surface of the cathode particles decreases, and the concentration gradient and liquid phase ohmic voltage drop in the electrolyte decrease, which is reflected in a decrease in the 60A temperature rise and an increase in the 8A / 40A cycle retention rate. It can be seen that the cathode material region length of 1700mm to 1800mm in this invention can take into account both area gain and cylindrical winding manufacturability.
[0105] Comparing the cylindrical lithium-ion battery structural parameters and performance data of Examples 15, 16, and Comparative Example 4, it can be seen that the equivalent positive electrode surface capacity Q p It is a key intermediate variable connecting capacity and active area; in Examples 15 and 16, Q p They are 1.88mAh / cm³ respectively. 2 and 2.00mAh / cm2 It is still in the low areal capacity range, the diffusion distance in the thickness direction of the positive electrode is controlled, and the electrolyte can enter the pores more fully; in Comparative Example 4, Q p Increased to 2.30mAh / cm 2 Although the capacity increases, the load per unit area of the positive electrode active material layer increases, and the concentration polarization in the thickness direction intensifies, leading to a worsening of both the 60A temperature rise and cycle degradation; Q p With S p J 60 The common constraints can avoid simply increasing the areal density to gain capacity at the expense of rate performance.
[0106] Comparing the cylindrical lithium-ion battery structural parameters and performance data of Examples 1, 14, and 22, it can be seen that the difference between the length of the negative electrode region and the length of the positive electrode region affects the lithium-ion receiving boundary in the beginning and end regions. In Example 1, the difference between the length of the negative electrode region and the length of the positive electrode region (L...) n -L p The diameter of the winding diameter is 55mm in Example 14 and 40mm in Example 22, both of which ensure that the negative electrode covers the positive electrode end in the winding direction. However, when the difference in Example 22 is reduced to 5mm, fluctuations in winding tension, thermal shrinkage of the electrode sheet, or assembly misalignment may cause insufficient negative electrode capacity to be absorbed in local positive electrode areas, increasing the risk of edge lithium plating and amplifying capacity decay during high-rate charge-discharge cycles. n -L p The thickness can be preferably 30mm to 90mm, and more preferably 40mm to 75mm.
[0107] Comparing the cylindrical lithium-ion battery structure parameters and performance data of Examples 1 and 17 with Comparative Examples 5 and 6, it can be seen that N / P determines the magnitude of the negative electrode capacity redundancy relative to the positive electrode capacity. The N / P of Example 1 is 1.05, and the N / P of Example 17 is 1.07, both of which can provide adequate capacity redundancy for lithium intercalation in the negative electrode during high-rate charging and avoid excessively low local potential of the negative electrode. However, increasing the N / P of Comparative Example 5 to 1.12 will result in ineffective mass and increased core thickness. The N / P of Comparative Example 6 is reduced to 0.98, resulting in insufficient reversible capacity of the negative electrode. The beginning, end, or adjacent areas of the tab are more likely to approach a fully intercalated state during high-rate cycling, thereby increasing the risk of lithium plating and impedance growth. Limiting the N / P to 1.02-1.09 is a more reasonable range.
[0108] Comparing the structural parameters and performance data of the cylindrical lithium-ion batteries in Examples 1, 18, and 23, it can be seen that the silicon-carbon material content affects the specific capacity, areal density, and interface stability of the negative electrode. In Example 1, the silicon-carbon material accounts for 6.0% of the negative electrode material, which can improve the negative electrode capacity and maintain the areal density of the negative electrode at approximately 5.20 mg / cm³. 2Furthermore, lower compaction is used to reduce ion transport resistance; in Example 18, the silicon-carbon material accounts for 5.0% of the anode material, and a low anode single-sided areal density is still maintained; while in Example 23, when the proportion of silicon-carbon material is reduced to 1.0%, the anode single-sided areal density needs to be increased to 6.20 mg / cm³ to maintain a 4 Ah capacity. 2 This leads to increased tortuosity of the negative electrode channel, exacerbating the 50A overpotential and cycle decay; the proportion of silicon-carbon material in the negative electrode material can be 3% to 10%, more preferably 5% to 7%.
[0109] Comparing the cylindrical lithium-ion battery structural parameters and performance data of Examples 1, 19, and 24, it can be seen that the thickness of the current collector copper foil is directly related to the cylindrical core space and the low surface flow structure of the long electrode sheet. The current collector copper foil thickness in Example 1 is 6.0 μm, and in Example 19 it is 5.5 μm, both of which free up radial space in the core, keeping the lengths of the positive and negative electrode material areas within the long electrode sheet range. However, when the current collector copper foil thickness in Example 24 increases to 8.0 μm, the space available for the active coating, separator, and winding allowance within the same housing space is compressed, the length of the positive electrode material area decreases to 1600 mm, and the single-sided active area of the positive electrode decreases. 60 The thickness of the current collector copper foil is preferably 5 μm to 7 μm and should be defined together with the area of the long electrode.
[0110] Comparing the cylindrical lithium-ion battery structural parameters and performance data of Examples 1, 20, 21 and 25, it can be seen that the electrolyte composition affects the silicon-carbon anode interface film, the high-potential side reaction of the cathode, and the impedance increase after high-temperature storage. Example 1 uses a baseline system containing lithium hexafluorophosphate, carbonate solvent, low-viscosity co-solvent of acetate, and lithium difluorophosphate additives. Examples 20 and 21 further adjust the content of low-viscosity co-solvent of acetate and film-forming additives to improve high-temperature storage recovery and some high-temperature cycling performance. However, Example 25 does not add lithium difluorophosphate additives and has too high a content of low-viscosity co-solvent of acetate, resulting in poorer interface film stability and gas generation control.
[0111] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A cylindrical lithium-ion battery, characterized in that, The equivalent positive electrode surface capacity Q of the cylindrical lithium-ion battery p 1.80mAh / cm 2 -2.25mAh / cm 2 ; The equivalent positive electrode current density J of the cylindrical lithium-ion battery during 40A discharge is... 40 18mA / cm 2 -22.04mA / cm 2 The double-sided equivalent positive electrode current density J during 50A discharge. 50 22mA / cm 2 -27.55mA / cm 2 The double-sided equivalent positive electrode current density J during 60A discharge. 60 27mA / cm 2 -33.06mA / cm 2 ; The length L of the positive electrode region of the cylindrical lithium-ion battery p The width W of the positive electrode material area is 1500mm-1850mm. p The length L of the negative electrode material region is 59mm-62mm. n The length L of the positive electrode material region is greater than that of the positive electrode material region. p Width W of the negative electrode material region n The width W of the positive electrode material region is greater than that of the positive electrode material region. p ; The positive electrode active material in the positive electrode material region includes a high-nickel layered lithium transition metal oxide. The negative electrode active material in the negative electrode material region includes artificial graphite and silicon carbide materials; The equivalent negative electrode surface capacity Q of the cylindrical lithium-ion battery n With equivalent positive electrode surface capacity Q p The ratio N / P is 1.02-1.
09.
2. The cylindrical lithium-ion battery according to claim 1, characterized in that, The length L of the positive electrode material region p The width W of the positive electrode material area is 1700mm-1800mm. p It is 60mm-61mm; Preferably, the length L of the negative electrode material region n The length L of the positive electrode material region p 30mm-90mm larger; Preferably, the width W of the negative electrode material region n Width W of the positive electrode material region p Larger by 1mm-3mm.
3. The cylindrical lithium-ion battery according to claim 2, characterized in that, The equivalent positive electrode surface capacity Q p 1.86mAh / cm 2 -2.05mAh / cm 2 ; Preferably, the single-sided active area S of the positive electrode p 900cm 2 -1120cm 2 The preferred size is 1020cm. 2 -1100cm 2 ; Preferably, the single-sided active area S of the negative electrode n With the positive electrode single-sided active area S p The ratio is 1.03-1.
12.
4. The cylindrical lithium-ion battery according to claim 1, characterized in that, Based on transition metal elements, the molar percentage of nickel in the high-nickel layered lithium transition metal oxide is 80%-93%.
5. The cylindrical lithium-ion battery according to claim 1, characterized in that, The areal density of the positive electrode sheet is 9.8 mg / cm³. 2 -11.3mg / cm 2 The preferred concentration is 10.2 mg / cm³. 2 -10.9mg / cm 2 ; Preferably, the compaction density of the positive electrode sheet is 3.40 g / cm³. 3 -3.60g / cm 3 The preferred value is 3.45 g / cm³. 3 -3.55g / cm 3 .
6. The cylindrical lithium-ion battery according to claim 1, characterized in that, The mass percentage of silicon-carbon material in the negative electrode active material is 3%-10%; Preferably, the areal density of the negative electrode sheet on one side is 4.7 mg / cm³. 2 -5.8mg / cm 2 ; Preferably, the compaction density of the negative electrode sheet is 1.42 g / cm³. 3 -1.58g / cm 3 ; Preferably, the negative electrode current collector comprises copper foil; Preferably, the thickness of the negative electrode current collector is 5μm-7μm.
7. The cylindrical lithium-ion battery according to claim 1, characterized in that, The electrolyte used in the cylindrical lithium-ion battery includes lithium salt, organic solvent, and additives. Preferably, the lithium salt comprises lithium hexafluorophosphate; Preferably, the organic solvent includes at least one of cyclic carbonates, chain carbonates, and low-viscosity cosolvents of acetates; Preferably, the additives include at least one of lithium difluorophosphate additives, fluorocarbonate film-forming additives, sulfonate lactone additives, and boron-containing lithium salt additives. Preferably, based on the total mass of the electrolyte, the electrolyte contains 0-15.0% by mass of acetate-based low-viscosity co-solvent, 2.0%-2.5% by mass of fluorocarbonate-based film-forming additives, and 0.5%-1.0% by mass of lithium difluorophosphate additives; Preferably, the separator width used in the cylindrical lithium-ion battery is greater than the width W of the negative electrode material region. n ; Preferably, the width of the diaphragm is 63.5mm-66.5mm; Preferably, the length of the separator is greater than the length L of the negative electrode material region. n ; Preferably, the length of the separator is proportional to the length L of the positive electrode material region. p The difference is 100mm-220mm.
8. The cylindrical lithium-ion battery according to any one of claims 1-7, characterized in that, Under the initial conditions of 25℃ and 4.0V, the cylindrical lithium-ion battery has a discharge time of not less than 170s when discharged to 2.5V at a constant power of 200W and not less than 150s when discharged to 2.5V at a constant power of 220W. Preferably, at 25°C and a voltage window of 4.2V-2.5V, the cylindrical lithium-ion battery retains a capacity of not less than 78% after 1000 cycles of charging at 8A and discharging at 50A, or a capacity of not less than 80% after 1000 cycles of charging at 14A and discharging at 40A. Preferably, the cylindrical lithium-ion battery has a DCR of no more than 8.0 mΩ at 25°C and 100% SOC, and an overpotential of no more than 0.30V under discharge conditions of 25°C and 50A. Preferably, the highest surface temperature of the cylindrical lithium-ion battery when discharged at 40A, 50A and 60A at 25°C and 100% SOC is no higher than 60°C, 68°C and 73°C, respectively.
9. A method for preparing a cylindrical lithium-ion battery according to any one of claims 1-8, characterized in that, Includes the following steps: A positive electrode, a separator, and a negative electrode are wound together to form a wound electrode assembly. The wound electrode assembly is then placed into a housing and injected with electrolyte. After formation, aging, and capacity testing, the cylindrical lithium-ion battery is obtained.
10. The application of a cylindrical lithium-ion battery according to any one of claims 1-8 in a battery module, battery pack or electrical device.